Adenovirus-Mediated Gene Transduction of Pancreatic Tumour Cells Lines - Salehhuddin, Hamdan; Pandha, H. S.; Blair, G. E. (2006)
Pancreatic cancer is often a fatal disease due to its poor response to existing therapies. Thus new therapeutic approaches must be developed. The aim of this study was to evaluate the susceptibility of pancreatic cell lines to adenovirus-mediated transduction and to determine the expression of surface coxsackie B and adenovirus receptor (CAR). Five human pancreatic cancer cell lines were transduced using a recombinant adenovirus type 5 expressing enhanced green fluorescent protein (Ad5EGFP) and the expression of EGFP was analysed by flow cytometry. The cell lines varied in transduction efficiency, ranging from less than 1% to more than 30% cells expressing EGFP and susceptibility of cell lines to Ad5EGFP transduction has a positive correlation with the level of surface CAR expression and its presence may be a limiting step for efficient adenovirus transduction. These results suggest that gene therapy of pancreatic tumours is feasible, but then the status of CAR expression in the tumour needs to be evaluated.